2006
DOI: 10.1086/498110
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Chemical Evolutionary Histories of the Galactic Thin Disk and Thick Disk Stellar Populations

Abstract: We have studied 23 long-lived G dwarfs that belong to the thin disk and thick disk stellar populations. The stellar data and analyses are identical, reducing the chances for systematic errors in the comparisons of the chemical abundance patterns in the two populations. Other elements share this same behavior, including Sc, Co, and Zn, suggesting that at least in the chemical enrichment history of the thick disk, these elements were manufactured in similar-mass stars. The heavy s-process elements Ba, La, Ce, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 82 publications
10
67
0
Order By: Relevance
“…Scandium Figure 3a shows the abundance result for Sc; it is evident that the [Sc/Fe] Our results are consistent with previous works, including Prochaska et al (2000), Nissen et al (2000), Allende Prieto et al (2004), Reddy et al (2006), Brewer & Carney (2006), Adibekyan et al (2012), and Ishigaki et al (2013). It is worth noting that the sample studied in Ishigaki et al (2013) reaches [Fe/H] ≈ −3 with solar [Sc/Fe], confirming what we see from the few metal-poor stars analyzed in this work.…”
Section: General Abundance Trendssupporting
confidence: 91%
See 1 more Smart Citation
“…Scandium Figure 3a shows the abundance result for Sc; it is evident that the [Sc/Fe] Our results are consistent with previous works, including Prochaska et al (2000), Nissen et al (2000), Allende Prieto et al (2004), Reddy et al (2006), Brewer & Carney (2006), Adibekyan et al (2012), and Ishigaki et al (2013). It is worth noting that the sample studied in Ishigaki et al (2013) reaches [Fe/H] ≈ −3 with solar [Sc/Fe], confirming what we see from the few metal-poor stars analyzed in this work.…”
Section: General Abundance Trendssupporting
confidence: 91%
“…In Figs. 4c and d, the LTE case shows that the trends for the young and old populations are similar and difficult to distinguish, as also pointed out in Brewer & Carney (2006). In the NLTE case, a difference between old and young population seems to be present in the metallicity range −0.6 [Fe/H] −0.1.…”
Section: Thin and Thick Disk Trendsmentioning
confidence: 56%
“…We found a significant fraction of these stars (∼40%) to be most consistent with the thick disk. The abundances of these metal-poor thick-disk stars had high [α/Fe] ratios, consistent with rapid star formation, which agrees with previous studies of much smaller samples of metal-poor thick-disk stars (Fulbright 2002;Bensby et al 2003;Brewer & Carney 2006;Reddy et al 2006;Reddy & Lambert 2008;AlvesBrito et al 2010). Further, we found that the [α/Fe] ratios were indistinguishable from those of the halo, indicating that the halo and the thick disk shared a similar massive-star IMF and similar efficient mixing of enriched material into the ISM.…”
Section: Introductionsupporting
confidence: 90%
“…A number of studies have claimed ∼0.2 dex [Sc/Fe] enhancements in metal-poor stars of the MW halo and thick and thin disks (e.g., Zhao & Magain 1990;Nissen et al 2000;Carretta et al 2002;Cohen et al 2004;Brewer & Carney 2006;Reddy et al 2006). However, it has been pointed-out that errors in log g f values and/or the treatment of hyperfine structure (e.g., Gratton & Sneden 1991;Prochaska & McWilliam 2000) Error bars account for random and systematic uncertainties.…”
Section: Scandium: No Evidence For Population III Enrichmentmentioning
confidence: 99%